2019
DOI: 10.12732/ijam.v32i3.6
|View full text |Cite
|
Sign up to set email alerts
|

On a Class of Solutions for the Hyperbolic Diophantine Equation

Abstract: Let µ ≥ 2 be a natural number. In this paper, we find all the solutions of the Hyperbolic Diophantine equations D : x 2 − (µ 2 − µ)y 2 − (4µ + 2)x + (6µ 2 − 6µ)y − (5µ − 13)µ = 0 over Z. We also derive some recurrence relations on the integer solutions (x n , y n ) of D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 3 publications
(2 reference statements)
0
2
0
Order By: Relevance
“…) for are found by Kannan et al [19]. It is also shown that the Diophantine equation , -, -,is solvable in prime variables , and with some conditions on [20].…”
Section: Introductionmentioning
confidence: 81%
“…) for are found by Kannan et al [19]. It is also shown that the Diophantine equation , -, -,is solvable in prime variables , and with some conditions on [20].…”
Section: Introductionmentioning
confidence: 81%
“…The two key functions of cryptography are encryption and decryption. Data properly encryption and decryption are very much necessary in communication systems [27].…”
Section: Proposed Workmentioning
confidence: 99%
“…There are a few quartic Diophantine equations that must be solved to arrive at the non-existence. To resolve those equations, the method of variable transformation is adopted as in (6,7) . Also, the basic number theoretic concepts are retrieved from "Fundamental Perceptions in Contemporary Number Theory" (8) , contributed by J.…”
Section: Introductionmentioning
confidence: 99%